2011
DOI: 10.3109/14767058.2011.629252
|View full text |Cite
|
Sign up to set email alerts
|

Lutein and zeaxanthin supplementation in preterm infants to prevent retinopathy of prematurity: a randomized controlled study

Abstract: L/Z supplementation was ineffective in preventing ROP in preterm infants and did not affect the outcome at discharge of our patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
60
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 30 publications
2
60
0
Order By: Relevance
“…[63][64][65] However, clinical trials that tested the efficacy of various antioxidants, including vitamin E, N-acetylcysteine, and lutein, have been inconclusive or have shown unacceptable side effects in infants with retinopathy of prematurity. 66,67 Studies of vitamin E supplementation in preterm infants were stopped because of sepsis and necrotizing enterocolitis, but a later meta-analysis of some studies suggested that vitamin E supplementation was associated with reduced stage 3 retinopathy of prematurity. 68 Thus, although it appears that oxidative stress promotes some aspects of severe retinopathy of prematurity, broad inhibition by antioxidants may not be safe.…”
Section: Antioxidantsmentioning
confidence: 99%
“…[63][64][65] However, clinical trials that tested the efficacy of various antioxidants, including vitamin E, N-acetylcysteine, and lutein, have been inconclusive or have shown unacceptable side effects in infants with retinopathy of prematurity. 66,67 Studies of vitamin E supplementation in preterm infants were stopped because of sepsis and necrotizing enterocolitis, but a later meta-analysis of some studies suggested that vitamin E supplementation was associated with reduced stage 3 retinopathy of prematurity. 68 Thus, although it appears that oxidative stress promotes some aspects of severe retinopathy of prematurity, broad inhibition by antioxidants may not be safe.…”
Section: Antioxidantsmentioning
confidence: 99%
“…To date, four RCTs have investigated the relationship between xanthophylls and ROP [17,[143][144][145]. All studies included preterm infants <33 weeks gestational age.…”
Section: Macular Xanthophyll Lutein/zeaxanthin and Retinopathy Of Prementioning
confidence: 99%
“…Capeding et al addressed safety, tolerance and growth (Capeding et al, 2010). There have been three papers suggesting a potential influence of lutein supplementation on the prevention on the retinopathy of prematurity (Dani et al, 2012;Manzoni et al, 2013;Romagnoli et al, 2011). The first one did not showed any effect of lutein/zeaxanthin supplementation.…”
Section: Is There a Translation To Functionality?mentioning
confidence: 99%